Neoliberalism, ethics and the social responsibility of psychology dialogues at the edge - Carabbio-Thopsey, Sara 1992-; Goodman, David 1980-; Macdonald, Heather (Psychologist) (Routledge, 2022)
"This volume encompasses deeply critical dialogues that question how the field of psychology exists within and is shaped by the current neoliberal political context. Spanning from psychoanalysis to post-colonial theory, these far-reaching discussions consider how a greater ethical responsiveness to human experience and sociopolitical arrangements may reopen the borders of psychological discourse. With the understanding that psychology grows in the soil of neoliberal terrain and is a chief fertilizer for neoliberal expansion, the interviews in this book explore alternative possibilities for this field of study might function. By offering their own unique responses regarding the current condition of their respective disciplines, these scholars critically consider the current conceptual frameworks that set the theoretical boundaries of psychology, and contemplate the ethical responsibilities currently affecting the field. This book will prove essential for scholars and students across several disciplines including psychology, philosophy, ethics, and post-colonial and socio-cultural studies, as well as practicing mental health professionals with an interest in the importance of psychological and social theory"-- Provided by publisher.